Chemical and Biological Properties of Potted-Soil for Strawberry Cultivation - Hindersah, Reginawanti; Kamaluddin, Nadia Nuraniya; Akustu, Masako; Herdiyantoro, Diyan (Agrikultura, 2023)
Strawberries in tropical West Java are cultivated intensively in potted soil but the substrate condition received less attention. The objective of this descriptive research was to evaluate the chemical and macronutrient profile in potted-soils for strawberry cultivation, and to determine beneficial microbes’ population in root-free bulk soil and rhizosphere of potted-strawberry.  The soil samples collected from 12-months and one-month-old potted strawberry; both contained Inceptisols soil order with 10 t/ha and 25 t/ha manure respectively. The proximate analysis was performed using Association of Official Analytical Chemists Method. The microbial enumeration was performed by Serial Dilution Plate Method in specific medium. The results showed that potted soils were not saline, but slightly acid, low in organic carbon and high in cation exchange capacity. The soil reactions were suitable for strawberry but the electrical conductivity was too low for strawberry growth. The potted soils have low to very low carbon to nitrogen ratio, but high in total nitrogen and very high in potential P2O5 and K2O. The population of phosphate-solubilizing bacteria, nitrogen-fixing Azotobacter, total bacteria and total fungi in old potted soil were low; but its counts were increased in manure-treated potted soil. The ratios of bulk soil to rhizosphere microbial count were only 1.0-1.25. The study verified that the doses of organic matter should be increased, while decreasing the chemical fertilizer level.